From Universal to Selective Social Housing Policy - Lis, Piotr (Acta Universitatis Lodziensis. Folia Oeconomica, 2018)
The aim of this article is an attempt to assess the directions of changes in the social housing policy as part of the state’s policy on housing within the European Union member states. This study highlights the fundamental conditions for conducting effective housing policy. These conditions include a proper allocation of the social housing stock, including the terms and conditions for entering and leaving the stock, a right choice of target groups for the stock, an adequate form of organisation of social housing construction fitted for the social housing policy model, including the terms and scope of participation of the private sector in social housing construction, a proper division of the responsibility for fulfilling the social goals between the central and local authorities, as well as specifying rational scopes of legal protection for both the residents and owners of the social housing stock.